The Types of Phasmida in the Zoological Institute, Russian Academy of Sciences, St. Petersburg (ZMAS) - Brock, Paul D. (Zootaxa, 2007)
Type specimens of 67 taxa of Phasmida (including probable type specimens of 24 taxa) have been located in the Zoological Institute, Russian Academy of Sciences, St. Petersburg. The species are listed alphabetically, with the number of specimens, sex and locality data.